Comparison of conventional and extractive fermentation using aqueous two-phase system to extract fibrinolytic proteases produced by Bacillus stearothermophilus DPUA 1729 - Cruz Filho, Raimundo Felipe da (2020)
Fibrinolytic enzymes have been considered promising for treatment and protection of healthy circulation due its ability to dissolve the fibrin in blood clots. Extractive fermentation is a not explored and efficient downstream process which segregates the desired product simultaneously in a fermentation process fast and economically. Extraction of fibrinolytic enzymes by Bacillus stearothermophilus DPUA 1729 employing conventional aqueous two-phase systems (ATPS) and extractive fermentation with ATPS was evaluated. The results of both systems were compared using a factorial design with PEG molar mass, PEG and salt concentrations as independent variables and extraction parameters as a response. In all conditions evaluated it was observed a similar partitioning of fibrinolytic enzymes through the phases, both in conventional ATPS and extractive fermentation. Salt concentration and interaction among PEG and salt concentration influenced in the partition coefficient. The fibrinolytic activity was determined by hydrolysis of fibrin in plate using the extract of one condition from extractive fermentation. The zone degradation presented a diameter of 7.03 ± 0.94 mm. In conclusion, there was no significant difference among the results obtained using conventional ATPS and extractive fermentation, however, the second one presents more advantages and can integrate production and extraction in one single step, reducing the costs.